(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Many problems in mathematics are related to proofs, and such problems can be solved using various methods: elementary methods, using properties, and the method of mathematical induction. Depending on the formulation of the problem, each of these methods may offer different levels of convenience.